Volksrepublik China. Neue Fakten zur Ankunft des Weizens in China. Die Arbeiten des Jahres 2017 - Wagner, Mayke; Long, Tengwen; Leipe, Christian; Jin, Guiyun; Guo, Rongzhen; Schröder, Oskar; Tarasov, Pavel E. (e-Forschungsberichte des DAI, 2018)
Directly dated bread wheat caryopses from six key archaeological sites in Shandong and Liaoning Peninsula and the application of Bayesian modelling to the newly obtained and a systematic collection of published data were used to reconstruct the chronology of wheat appearance in different regions of China. The results do not support the hypothesis of a progressive spread of wheat farming from West to East China, but instead corroborate transmission to lower Yellow River elites around 2600 BC as an exotic good through cultural interaction with the Eurasian steppe along north-south routes.